A Review on Current Methods of De-Icing and an Idea for Designing an Autonomous Robot for De-Icing - P. Srinivas Verma, Dr; Sidharth Sarat Raj, Batchu; Sainath, Sandopu; Kailash Narsingh Rao, Eyerrmshetty (International Journal of Engineering and Technology, 2018)
Extensive need regarding research and development of new techniques regarding transmission conductor de-icing is observed with the current methods available, are highly unsustainable to rely on as they are risky not only to the power system stability but also the lives of people and operations in the load area. This paper holds a technique and an idea for ice removal mechanism of transmission line that could be easily implemented, mass produced and works autonomously along with review on current methods. A robot for every span of transmission line which is self-sustained and completely autonomous to de-ice the transmission line with extremely cost efficient is objective being for this paper. Prototype model, working for dummy transmission system (without ice) shows good results for being applied to an original transmission line. De-icing here is obtained by applying constant friction on the transmission conductor which apparently does not cause damage to health and wear of the conductor. All the considerable measurements for that span of electrical system are tired to be met while designing. The performance approach is evaluated through practical simulation of a likely prototype which is subjected to be real. Â Â